2017
DOI: 10.1182/blood-2016-09-742296
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of circulating exosomal miRNAs in multiple myeloma

Abstract: Exosomes, secreted by several cell types, including cancer cells, can be isolated from the peripheral blood and have been shown to be powerful markers of disease progression in cancer. In this study, we examined the prognostic significance of circulating exosomal microRNAs (miRNAs) in multiple myeloma (MM). A cohort of 156 patients with newly diagnosed MM, uniformly treated and followed, was studied. Circulating exosomal miRNAs were isolated and used to perform a small RNA sequencing analysis on 10 samples and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
237
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(245 citation statements)
references
References 40 publications
6
237
2
Order By: Relevance
“…Previous studies have shown that plasma levels of miRNA are associated with ISS disease stage and PFS in myeloma . The expression levels of miR‐16 and miR‐20a, along with those of let‐7a, let‐7b, let‐7i, miR‐15b, and miR‐20a, were significantly abnormal in myeloma serum, and microRNAs showed different expression in serum from patients with monoclonal immunoglobulin‐related diseases, including monoclonal gammopathy of undetermined significance (MGUS), SMM, and MM . Exosomes, which are formed by membraned vesicles, contain microRNAs, mRNAs, and proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that plasma levels of miRNA are associated with ISS disease stage and PFS in myeloma . The expression levels of miR‐16 and miR‐20a, along with those of let‐7a, let‐7b, let‐7i, miR‐15b, and miR‐20a, were significantly abnormal in myeloma serum, and microRNAs showed different expression in serum from patients with monoclonal immunoglobulin‐related diseases, including monoclonal gammopathy of undetermined significance (MGUS), SMM, and MM . Exosomes, which are formed by membraned vesicles, contain microRNAs, mRNAs, and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Previous studies have shown that exosomal microRNAs may function as diagnostic biomarkers in numerous malignancies, including MM. 12,13 However, the role of exosomal microRNAs in the progression of MM has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Two miRNAs‐derived exosomes, miR‐18a and let‐7b, were observed to be considerably associated with poor outcomes of patients regarding the overall and progression‐free survival. Importantly, let‐7b and miR‐18a were predictive in an independent manner even after adjusting for the ISS and particular cytogenetic abnormalities univariate and in multivariate analyses . Exosomes which may contain miRNAs could be secreted from MM cells and regulates expression of genes such as FIH‐1 and HIF‐1 in endothelial cells and promote angiogenesis (Figure ).…”
Section: Exosomes and MMmentioning
confidence: 99%
“…It is worth noting that ncRNAs may alter their expression in patients after treatment and change with MM progression, which gives them the ability to predict the prognosis and drug response. Specific exosomal miRNAs (let‐7b and miR‐18a) were critical in defining worse prognosis in terms of progression‐free survival (PFS) and overall survival (OS) in newly diagnosed MM patients (Manier et al, ). Sometimes, the combination of ncRNAs and other clinicopathological parameters could gain a one‐plus‐one‐greater‐than‐two effect.…”
Section: Values Of Targeting Ncrnas In MMmentioning
confidence: 99%